Bank soundness and macroeconomic policy - Lindgren, Carl-Johan.; Garcia, G. G.; Saal, Matthew I. (Washington, D.C. : International Monetary Fund, 1996)
The book takes a global view of the causes and consequences of banking sector problems and points to ways in which banking systems can be strengthened nationally and internationally.
Includes bibliographical references (p. 205-215).
rua 18/07/16
Loans
Keywords: Banks and banking; Financial institutions; Economic policy; Macroeconomics